Tony’s Law: Seeking to promote regulations for reliable software for the long-term prosperity of the software industry. - Feitelson, Dror G. (Communications of the ACM, 2019)
The author presents his thoughts on the need for regulation in the software industry to ensure long-term prosperity. He cites comments from computer programmer Tony Hoare that predicted the need for laws governing computer software to prevent malpractice and security risks.